MENILAI KESEHATAN BUMN KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA SEBAGAI AKIBAT MENINGKATNYA PROYEK INFRASTRUKTUR PEMERINTAH - Agung Dinarjito (SUBSTANSI, 2018)
In order to improve equitable development in Indonesia, the government has boosted infrastructure development. Government believes that infrastructure is the most influencing factor of economic growth. However, to carry out the mission, the Government asks all parties to take part in the infrastructure development process. This is because the Government budget is not enough to implement all these projects. State-Owned Enterprise (SOE) is one of the parties requested by the Government to participate in infrastructure development projects. Because the infrastructure project is costly and not fully financed by the Government, it has forced SOEs to seek other sources of funding, one of them through debt. This study aims to determine the health condition of state-owned construction as a motor of government infrastructure development and predict financial distress in the future. This research is a descriptive quantitative research that try to explain the result of calculation by using certain method. To measure the health condition, the author uses five models, namely financial ratios, grover, altman z-score, springate and zmijewski. The results of the research indicate that there are different results of the methods used related to the health condition of state-owned construction.